Use mathematical induction to prove that for each integer n2 0, if F, F F ... is the Fibonacci sequence, then ged(F.. Fa) - 1. (The definition of ged is given in Section 4.10.) You may use the following lemma in the proof. Lemma: If a and b are any integers not both zero, and if g and rare any integers such that a- bg +r, then god(a, b) - ged(b, r). Proof (by mathematical induction): Let the property P(n) be the equation ged(F. F) - 1. Show that P(0) is true: Select P(0) from the choices below. OF, F1 O gcd(F F) = 1 • ged(F,. F) = 1 O gcd(F,. F;) = 1 The selected statement is true by definition of the Fibonacci sequence. Show that for each integer k2 0, if P(k) is true, then P(k + 1) is true: Let k be any integer with kz 0, and suppose that P(k) is true. Select P(k) from the choices below. • gcd(F.F) -1 O gcd(F, . 3 Fa + 3) = 1 O ged(F F) - 1 O gcd(F, . F+ ) = 1 (This is P(k), the inductive hypothesis.] We must show that P(k + 1) is true. Select P(k + 1) from the choices below. O ged(Fz F) - 1 • gcd(F,. F.)-1 O ged(F,. 3 Fn ) = 1 O gcd(F, . 3 F,) = 1 Now F F..+F by defntion of the Fibonacci sequence V . Moreover, since F,.2=F+F, can be rewritten as F,+2F+1+F, the lemma can be applied with a= and r Select the result of applying the lemma from the choices below. O ged(F,. F) - ged(F,. F) O gcd(F, - 1 F) = gcd(F, - 1. F;) • ged(F.. 2. F. ;) = gcd(F, . 1• F2) So, by applying the inductive hypothesis, we can conclude that ged(F [as was to be shown].

Advanced Engineering Mathematics
10th Edition
ISBN:9780470458365
Author:Erwin Kreyszig
Publisher:Erwin Kreyszig
Chapter2: Second-order Linear Odes
Section: Chapter Questions
Problem 1RQ
icon
Related questions
Question
100%

Can you fill in the blanks for me?

Use mathematical induction to prove that for each integer \( n \geq 0 \), if \( F_0, F_1, F_2, \ldots \) is the Fibonacci sequence, then 

\[ \text{gcd}(F_{n+1}, F_n) = 1. \]

(The definition of gcd is given in Section 4.1.0.)

You may use the following lemma in the proof.

**Lemma**: If \( a \) and \( b \) are any integers not both zero, and if \( q \) and \( r \) are any integers such that \( a = bq + r \), then \( \text{gcd}(a, b) = \text{gcd}(b, r) \).

**Proof (by mathematical induction)**: Let the property \( P(n) \) be the equation \( \text{gcd}(F_{n+1}, F_n) = 1 \).

**Show that \( P(0) \) is true**: Select \( P(0) \) from the choices below.

- \( F_1 = F_0 = 1 \)
- \( \text{gcd}(F_1, F_0) = 0 \)
- \( \text{gcd}(F_1, F_0) = 1 \) (selected)
- \( \text{gcd}(F_2, F_1) = 1 \)

The selected statement is true by definition of the Fibonacci sequence.

**Show that for each integer \( k \geq 0 \), if \( P(k) \) is true, then \( P(k + 1) \) is true**: Let \( k \) be any integer with \( k \geq 0 \), and suppose that \( P(k) \) is true. Select \( P(k) \) from the choices below.

- \( \text{gcd}(F_{k+1}, F_k) = 0 \)
- \( \text{gcd}(F_{k+1}, F_k) = 1 \) (selected)
- \( \text{gcd}(F_{k+2}, F_{k+1}) = 1 \)
- \( \text{gcd}(F_{n+2} + F_{n+1}, 1) =
Transcribed Image Text:Use mathematical induction to prove that for each integer \( n \geq 0 \), if \( F_0, F_1, F_2, \ldots \) is the Fibonacci sequence, then \[ \text{gcd}(F_{n+1}, F_n) = 1. \] (The definition of gcd is given in Section 4.1.0.) You may use the following lemma in the proof. **Lemma**: If \( a \) and \( b \) are any integers not both zero, and if \( q \) and \( r \) are any integers such that \( a = bq + r \), then \( \text{gcd}(a, b) = \text{gcd}(b, r) \). **Proof (by mathematical induction)**: Let the property \( P(n) \) be the equation \( \text{gcd}(F_{n+1}, F_n) = 1 \). **Show that \( P(0) \) is true**: Select \( P(0) \) from the choices below. - \( F_1 = F_0 = 1 \) - \( \text{gcd}(F_1, F_0) = 0 \) - \( \text{gcd}(F_1, F_0) = 1 \) (selected) - \( \text{gcd}(F_2, F_1) = 1 \) The selected statement is true by definition of the Fibonacci sequence. **Show that for each integer \( k \geq 0 \), if \( P(k) \) is true, then \( P(k + 1) \) is true**: Let \( k \) be any integer with \( k \geq 0 \), and suppose that \( P(k) \) is true. Select \( P(k) \) from the choices below. - \( \text{gcd}(F_{k+1}, F_k) = 0 \) - \( \text{gcd}(F_{k+1}, F_k) = 1 \) (selected) - \( \text{gcd}(F_{k+2}, F_{k+1}) = 1 \) - \( \text{gcd}(F_{n+2} + F_{n+1}, 1) =
### Recursive Sequence Definition and Iteration

Consider the following recursively defined sequence:

\[
f_k = f_{k-1} + 2^k, \text{ for each integer } k \geq 2
\]
\[
f_1 = 1
\]

---

### Iteration to Guess an Explicit Formula

Fill in the blanks to use iteration to guess an explicit formula for the sequence.

1. \( f_1 = 1 \)
   
2. \( f_2 = f_1 + \boxed{2^2} = 1 + 2^2 \)
   
3. \( f_3 = f_2 + \boxed{2^3} = 1 + 2^2 + 2^3 \)
   
4. \( f_4 = f_3 + \boxed{2^4} = 1 + 2^2 + 2^3 + 2^4 \)

---

**Guess:**
\[
f_n = 1 + 2^2 + 2^3 + 2^4 + \ldots + \boxed{2^n}
\]

---

### Simplification Using Theorem 5.2.2

When Theorem 5.2.2 is used to simplify this expression, the result is:

\[
f_n = \left( \frac{\boxed{2^{n+1}} - 1}{2 - 1} \right) - 2
\]

And, when this expression is simplified, the result is:

\[
f_n = \boxed{2^{n+1}} - 3 \text{ for every integer } n \geq 1.
\]
Transcribed Image Text:### Recursive Sequence Definition and Iteration Consider the following recursively defined sequence: \[ f_k = f_{k-1} + 2^k, \text{ for each integer } k \geq 2 \] \[ f_1 = 1 \] --- ### Iteration to Guess an Explicit Formula Fill in the blanks to use iteration to guess an explicit formula for the sequence. 1. \( f_1 = 1 \) 2. \( f_2 = f_1 + \boxed{2^2} = 1 + 2^2 \) 3. \( f_3 = f_2 + \boxed{2^3} = 1 + 2^2 + 2^3 \) 4. \( f_4 = f_3 + \boxed{2^4} = 1 + 2^2 + 2^3 + 2^4 \) --- **Guess:** \[ f_n = 1 + 2^2 + 2^3 + 2^4 + \ldots + \boxed{2^n} \] --- ### Simplification Using Theorem 5.2.2 When Theorem 5.2.2 is used to simplify this expression, the result is: \[ f_n = \left( \frac{\boxed{2^{n+1}} - 1}{2 - 1} \right) - 2 \] And, when this expression is simplified, the result is: \[ f_n = \boxed{2^{n+1}} - 3 \text{ for every integer } n \geq 1. \]
Expert Solution
trending now

Trending now

This is a popular solution!

steps

Step by step

Solved in 4 steps

Blurred answer
Knowledge Booster
Logical Arguments
Learn more about
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, advanced-math and related others by exploring similar questions and additional content below.
Recommended textbooks for you
Advanced Engineering Mathematics
Advanced Engineering Mathematics
Advanced Math
ISBN:
9780470458365
Author:
Erwin Kreyszig
Publisher:
Wiley, John & Sons, Incorporated
Numerical Methods for Engineers
Numerical Methods for Engineers
Advanced Math
ISBN:
9780073397924
Author:
Steven C. Chapra Dr., Raymond P. Canale
Publisher:
McGraw-Hill Education
Introductory Mathematics for Engineering Applicat…
Introductory Mathematics for Engineering Applicat…
Advanced Math
ISBN:
9781118141809
Author:
Nathan Klingbeil
Publisher:
WILEY
Mathematics For Machine Technology
Mathematics For Machine Technology
Advanced Math
ISBN:
9781337798310
Author:
Peterson, John.
Publisher:
Cengage Learning,
Basic Technical Mathematics
Basic Technical Mathematics
Advanced Math
ISBN:
9780134437705
Author:
Washington
Publisher:
PEARSON
Topology
Topology
Advanced Math
ISBN:
9780134689517
Author:
Munkres, James R.
Publisher:
Pearson,